(untitled) (Journal of Hama University, 2019)
Introduction: The immediate placement of implants into fresh extraction socket has proven to be a safe and predictable procedure. The Purpose of this study was to evaluate the use of the platelet rich fibrin as a membrane in treatment peri-implant bone defect of immediate implants. materials and methods: fourteen implants were inserted into eleven adult patients (3male,8 female) with age average 46.5 years, indicated for extraction & immediate implant insertion. A venous blood sample of 10 cc was obtained for each single implant. After implant placement, the peri-implant defect was filled with natural blood then , a platelet rich fibrin membrane was used to cover the implant site. Clinical & radiographic evaluation was performed immediately and 6 months postoperatively to evaluate soft tissue healing & crestal bone changes and to assess the complications and the success rate . Results: After 6 months,the success rate was 100%, good soft tissue coverage was obtained except tow covered screw exposured. Radiographically, bone height showed at the mesial side 0.17 mm bone loose and in the distal side 0,45 mm bone loose. The vertical bone filling in defect was limited to 60,92 %. Conclusion: Platelet rich fibrin membrane with immediate implants is safe and predictable procedure to treat the peri-implant bone defect and provide good soft tissue coverage over the immediate implants with minimum degree of bone loosing and complications.